The Antinomy Of Corporate Criminal Law Enforcement In The Environment - Erwin Syahruddin (PT. Anagata Sembagi Education, 2025)
A corporation whose business activities are suspected of polluting and damaging the environment and having a major and important impact on the environment. Corporations in carrying out their business activities can cause environmental crimes, one of which is the Lapindo mud case. Article 116 of UUPPLH has regulated law enforcement on environmental criminal cases committed by corporations where criminal charges and criminal sanctions are imposed on business entities and/or people who give orders to commit such criminal acts or people who act as leaders of activities in such criminal acts. This research is a doctrinal legal research, in which this research examines the enforcement of criminal law for corporations that commit environmental crimes with a focus on the Lapindo mud case. The results of this study found that there are several obstacles in law enforcement of the Lapindo mud case, namely in terms of legal factors / laws, law enforcement factors, facilities or facilities, and cultural factors.